System Simulation of Pure Electric Vehicle Thermal Management with a Refrigerant Cooling Battery under Summer Conditions - Zhang Congzhe; Ye Fang; Guo Hang; Ma Chongfang (Zhileng xuebao)
Based on thermal management systems of pure electric vehicles, a thermal management scheme for a whole vehicle is proposed in this study under summer conditions. In this scheme, a parallel cooling system using refrigerant is developed for the batteries and cabin, and the heat transfer performance of the heat pipe is considered for heat exchange between the batteries and refrigerant. A liquid cooling system is used for the motor. The proposed thermal management system was tested using a system simulation under the New European Driving Cycle at 35 ℃. The results demonstrated that the temperature of the cabin reached 24 ℃ after 64 s. The cabin temperature then maintained a dynamic stability near the setting temperature. Moreover, the temperature of the batteries reached 25 ℃ after 68 s then maintained a stable temperature under the vehicle control strategy. An increase in motor temperature occurred at a low rate under an urban cycle and exhibited a rapid increase under an suburb cycle. However, the temperature of the motor was maintained within 80 ℃